Boosting Engineering Capabilities through Science Learning - Rohiat, Salastri; Widodo, Ari; Octaria Prajayanti, Atiek; Meta Pusparini, Rakai (Journal of Tropical Chemistry Research and Education, 2024)
This research aims to review increasing engineering capabilities through science learning using the case study method. The primary focus of the research is to understand how the integration of science concepts in the engineering curriculum can improve students' technical and analytical skills. The case study was conducted at a vocational high school that applies an interdisciplinary approach between science and engineering. Data was collected through classroom observations, interviews, and questionnaires. The research results show that students who are involved in science learning integrated with engineering can demonstrate an understanding of engineering concepts, problem-solving abilities, and critical thinking skills. In addition, teaching methods that focus on scientific projects and experiments have proven effective in building students' interest and motivation towards the field of engineering. This research concludes that science learning applied in an integrative manner can be an effective strategy in improving students' engineering capabilities